Avaliação do índice de melanina na pele de recém-nascidos prematuros e sua associação com a cronologia da gravidez - Paola Conceição da Silva (2019)
Background: Clinical scores to estimate the gestational age of neonates have considered skin texture and color as signals to judge physical maturity. Such scales use the size and darkness of areola around the nipple to grade skin characteristics, based on visual appearance. Melanin index (M-Index) is an optical skin parameter related to melanin content in the tissue. Prematurity detection in the birth scenario remains a challenge when antenatal parameters of dating are not available. This study is aimed to assess the M-Index of the skin, in premature newborns, and associated it with the pregnancy chronology. Methods: A cross-sectional study evaluated 80 premature newborns at birth according to eligibility criteria. A monochromatic narrow band light-emitting diode (LED) centered at 630 nm and a photo-diode, used as a sensor, quantified the skin pigmentation on the areola (n=78), the forearm (n= 80) and the sole of the foot (n=80) in a non–invasive approach. Paired-average difference of M-Index compared values among the three sites: the areola, the forearm and the sole of a newborn. The skin darkness values were described and M-indexes associated with the pregnancy chronology. The phototype of the skin of the mother, according to the Fitzpatrick scale, was compared with the M-Index of the newborn in the skin over the areola. Results: The gestational age of the newborns ranged from 24.1 to 36.9 weeks of gestation. Newborns with gestational age between 24 and 34 weeks had a melanin index with a median value of 38.3 (interquartile range = 10.5) in the areola, while the group with gestational age between 34 to <37 weeks had a median value of 41, 7 (interquartile range 8.9), p = 0.005. There was no association between melanin indices and the chronology of gestation when measured on the skin of the forearm or the sole of the foot. The values of the melanin index in the areola were higher in this region when compared to the regions of the forearm or in the sole area of the foot (p <0.001 for both). Conclusions: The analysis of the M-Index corroborated clinical antecedents of areolar darkness as a physical maturity marker in newborns. Such measureable values obtained by photometry have the potential to improve physical evaluation of maturity used in scores of prematurity.